Application of Concanavalin A during immune responsiveness skin-swelling tests facilitates measurement interpretation in mammalian ecology - Bílková, Barbora; Albrecht, Tomáš; Chudíčková, Milada; Holáň, Vladimír; Piálek, Jaroslav; Vinkler, Michal (Ecology and evolution, 2016)
The skin-swelling test is a simple and widespread method used in field ecological research to estimate cellular immune responsiveness in animals. This immunoecological test is based on measuring the magnitude of tissue swelling response at specific times following subcutaneous application of an experimental pro-inflammatory stimulant. In the vast majority of studies across vertebrate taxa, phytohemagglutinin (PHA) is used as a universal stimulant. Given the complexity of immune response activation pathways of PHA, however, interpretation of test results can be ambiguous. Goal of this study was to improve methodology of the skin-swelling test to decrease this ambiguity. Here, we present an alternative protocol aimed at facilitating interpretation of skin-swelling data for mammals. Based on previous evidence suggesting that mammalian T cells are readily activated by Concanavalin A (ConA) in vitro, we compared cellular immune responses in vivo to PHA and ConA as an alternative pro-inflammatory stimulant in mice. We measured magnitude of tissue swelling and compared it with intensity of blood cell infiltration into tissue over a 72-hour interval. Our results corroborate that PHA and ConA show important differences in both dynamics and response amplitude in rodents. ConA induces stronger swelling with a distinct leukocyte activity pattern and higher pro-inflammatory cytokine (interleukin 6 [IL-6] and interferon gamma[IFN-γ]) expression than PHA during peak response (24-h post-treatment). Furthermore, unlike PHA, magnitude of swelling was positively associated with cellular activity (number of neutrophils infiltrating tissue) following ConA injection. We conclude that ConA is the more suitable stimulant for skin-swelling tests in mammals. This is because of the molecular binding specificity in the two lectins, that is, ConA specifically activates T cells while PHA also triggers erythroagglutination. We propose that ConA be used in all future ecological testing in mammals as it exhibits better performance and its application facilitates immunological interpretation of skin-swelling test results.
Keywords: phytohemagglutinin; ecoimmunology; leucocytes; PHA‐induced hypersensitivity; field immunoecological research; evolutionary immunology; Concanavalin A; cytokine; histology; T‐cell‐mediated immunocompetence